Humanism In Project-Based Learning At Vocational High Schools: Building Human Values And Social Skills - Muhammad Akbar; Nurhasan Syah; Nizwardi Jalinus; Ernawati Ernawati; Fadhilah Fadhilah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This research discusses the values of Humanism in the PjBL learning process in SMK by building students' human values and social skills. This research aims to improve classroom learning by building students' human values and social skills. This research involves a literature review from various sources such as Scopus, Crossref, Sinta, Garuda, and ISSN-indexed articles. The method used to analyze the problem is the Prism method. The review process is carried out through several systematic stages, namely: Searching for keywords related to the problem using Publish Or Perish, obtaining 289 articles indexed by Scopus and Sinta, filtering related articles using Confidence, obtaining 24 articles that match the problem, then analyzing using the Vosviewer application to visualize the issues raised, determining research questions in each article. Humanism in PjBl is extremely successfully utilized in a number of learning processes that can greatly increase student learning outcomes, particularly in the area of students' thinking skills, according to the study findings based on a number of research questions.In addition, researchers found that in previously selected studies, Humanism in PjBL learning provides a more active learning atmosphere for students than ordinary (conventional) learning.